A critical review of relationship between corporate governance and firm performance: GCC banking sector perspective. Issue 1 (2nd February 2015) - Dalwai, Tamanna Abdul Rahman; Basiruddin, Rohaida; Abdul Rasid, Siti Zaleha
Abstract : Purpose: – The purpose of this paper is to evaluate existing studies on the relationship of corporate governance with firm performance in different regions and address the need for similar analysis for the Gulf Coperation Council (GCC) sector. The banking sector comprises the conventional and Islamic banks in the GCC sector and is important due to their ability to bring stability to this region. Existing studies that measure the relationship of GCC sector conventional banks and firm performance are limited. This study proposes a need for future research on corporate governance in the GCC region. Design/methodology/approach: – This paper will review and analyze the different empirical and theoretical contributions in establishing the relationship between corporate governance and firm performance. Findings: – This paper will create a focus for future research of measuring the impact of corporate governance mechanism on firm performance. The regulators will be encouraged to focus on more research studies for the GCC sector development in the field of corporate governance of the banking sector. Research limitations/implications: – The existing studies are valid and practicable for the region under study, and the results need not be applicable for other business environments. In addition, the evolving business and economic environment have always brought about inconsistent conclusions; thus, the period of study can always give varied results. Practical implications: – The analysis undertaken in this paper will address the literature gaps for the GCC banking sector and play an instrumental role for future studies by theoreticians and regulators. Originality/value: – This paper identifies the literature gaps for the GCC region and analyses the most applicable existing studies that can be useful for the banking sector corporate governance improvement. This paper will create opportunities for the future researchers.